Towards a Unified Way of Comparing the Electrocatalytic Activity mn4 Macrocyclic Metal Catalysts for o2 Reduction on the Basis of the Reversible Potential of the Reaction - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Recio-Cortes, F; Recio-Cortes, F; Zuñiga-Loyola, C; Zuñiga-Loyola, C (2014)
Sin Editorial Disponible